SOSIALISASI PENGUATAN KELOMPOK TERNAK VILLA SAIYO TIMBALUN DI KECAMATAN BUNGUS TELUK KABUNG KOTA PADANG - James Hellyward; Tevina Edwin; Riza Andesca Putra; Elita Amrina (BULETIN ILMIAH NAGARI MEMBANGUN, 2022)
A farmer group is a social forum, as a place for a group of people to work together to achieve a common goal. Farmer groups cannot be separated from social dynamics issues because every member of the farmer group has different characteristics. However, members of groups do not understand the dynamic group, so the farmer groups that have been formed are very vulnerable to disbanding or being inactive. The purpose of this socialization activity is to provide knowledge to the farmers of the Villa Saiyo Timbalun Livestock Group about group dynamics as an effort to help create an active, solid, and sustainable group and be able to develop a business so that it can increase group income for the welfare of the group. The implementation of the activity is carried out by the extension method, namely providing socialization of strengthening livestock groups about group dynamics to the target audience. The target of the implementation of the socialization of livestock groups strengthening to the community is a group of farmers in the city of Padang, namely the Villa Saiyo Timbalun livestock group in Bungus Teluk Kabung District. The Andalas University degree carried out on the livestock group of Villa Saiyo Timbalun, Bungus Timur Village, Bungus Teluk Kabung District was carried out well and smoothly. Farmers are enthusiastic about the implementation of this socialization of livestock group strengthening, which can be seen from the presence of both group members and breeders who are around the location of the livestock group strengthening socialization. the results of the socialization activity for strengthening livestock groups through counseling on the topic of group dynamics created an agreement between group members to return to active group business together. In addition, this activity provides additional knowledge for members to maintain the sustainability of the group, and make the group active again, and it is hoped that the group can run and develop group business so that group welfare can be achieved. The discussions also provided solutions that made the group return to running a business together. It can be concluded that the socialization activity for strengthening the livestock group was carried out well so that the objectives of the activity were achieved.